Dissertations - Naujokaitis , P. (Psichologija, 1972)
In Soviet Lithuania the amount of scholars of pedagogics and related branches of knowledge has been growing rapidly. In 1969-1972 (first half of 1972), i.e. in the course of 3.5 years, 74 theses were written and defended, whereas in 1949-1968, i.e. in the course of 20 years, 79 theses were defended. Thus, up to the lst of July, 1972 thirteen dissertations for a doctor’s degree and 140 dissertations for a candidate’s degree were written on pedagogics and related branches of knowledge. 89 of them were defended in Vilnius, 32 in Moscow, 24 in Leningrad, 3 in Kaunas, 3 in Tartu, l in Kiev and l in Minsk.